2013
DOI: 10.3109/00365548.2013.861608
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline therapy for infections due to carbapenemase-producing Klebsiella pneumoniae in critically ill patients

Abstract: Tigecycline appears to be an effective therapy for severe infections due to CPKP in critically ill patients. Mortality is related to the severity of the underlying disease. We observed no benefit from a higher maintenance dose of tigecycline, although the number of patients included in the study was too small to draw any general conclusions in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 30 publications
0
19
2
1
Order By: Relevance
“…In a recent randomized phase 2 trial, high dose TGC (100 mg q12h) was associated with better clinical efficacy than imipenem for treating nosocomial pneumonia caused by gram‐positive and gram‐negative bacteria in adult patients . Another retrospective study involving 15 patients receiving different doses of TGC for severe carbapenem‐resistant K pneumoniae infections reported that the overall 30‐day mortality rate was 33.3% for daily dose of 100 mg and 20% for daily dose of 200 mg . De Pascale et al reported that high dose TGC was not associated with additional toxicity in the treatment of serious infections in critically ill patients .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized phase 2 trial, high dose TGC (100 mg q12h) was associated with better clinical efficacy than imipenem for treating nosocomial pneumonia caused by gram‐positive and gram‐negative bacteria in adult patients . Another retrospective study involving 15 patients receiving different doses of TGC for severe carbapenem‐resistant K pneumoniae infections reported that the overall 30‐day mortality rate was 33.3% for daily dose of 100 mg and 20% for daily dose of 200 mg . De Pascale et al reported that high dose TGC was not associated with additional toxicity in the treatment of serious infections in critically ill patients .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported its use in combination with other antimicrobials in infections caused by carbapenemase-producing K. pneumoniae [11,12]. The use of HD tigecycline did not influence the outcome in a small series of critically ill patients with infections due to carbapenemase-producing K. pneumoniae [13]. In the study by De Pascale and colleagues [1], as in previous studies [10-13], this HD was not associated with undesirable effects.…”
mentioning
confidence: 99%
“…These effects were independent of the infection type, trial design, and study size [7]. However, TGC has been prescribed in life-threatening infections for which there were few or no alternative agents [911, 15, 24]. A high-dose TGC regimen has been shown to result in better outcomes in patients with severe infections caused by MDR bacteria [15].…”
Section: Discussionmentioning
confidence: 99%